Electrostatic layer-by-layer deposition of diamond nanoparticles onto substrate surfaces. (October 2022) - Yoshikawa, Taro; Tokuda, Norio; Makino, Yuto; Tsurui, Akihiko; Ieki, Ryosuke; Kojima, Ryouta; Liu, Ming; Mahiko, Tomoaki; Nishikawa, Masahiro
Abstract: Diamond nanoparticles (DNPs) are expected as splendid coating materials to give, e.g. corrosion resistance, anti-bacterial properties, and antireflection function. In this paper, we demonstrate a technique of electrostatic layer-by-layer deposition of DNPs onto substrate surfaces using DNP colloidal suspensions with different signs of zeta potentials alternately. The formed DNP layers are investigated in terms of film thickness, surface roughness, and homogeneity. Plus, those morphologies of DNP layers are theoretically correlated with the colloidal properties of DNP suspensions based on the electrostatic interaction potential energy between colloidal DNPs and substrate surfaces. Consequently, it turns out that the demonstrated technique enables formation of DNP thin layers with desired thickness, particle density, and surface roughness on substrate surfaces by controlling the ionic strength of colloidal DNPs.